2015
DOI: 10.1007/s10567-015-0199-1
|View full text |Cite
|
Sign up to set email alerts
|

Why are Religiousness and Spirituality Associated with Externalizing Psychopathology? A Literature Review

Abstract: This review explores the relation of religiousness and spirituality with externalizing psychopathology in adolescence given the heightened externalizing psychopathology during this developmental period. Utilizing a developmental psychopathology framework, previous literature is reviewed focusing on the diversity of pathways from religiousness and spirituality to externalizing psychopathology at multiple levels of analysis. Moreover, the pathways considered include both intraindividual factors (e.g., self-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 149 publications
1
30
0
1
Order By: Relevance
“…However, executive function did not mediate the link between religiousness and risk‐taking. The finding regarding emotion regulation is analogous to a range of studies that have found self‐regulation to be a mediator between religiousness and adolescent risk‐taking (see Holmes & Kim‐Spoon, 2016a for a review). Importantly, by simultaneously considering the two primary dimensions of self‐regulation as parallel mediators, this study sheds light on the specific pathway through which religiousness contributes to demoting adolescent risk‐taking.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, executive function did not mediate the link between religiousness and risk‐taking. The finding regarding emotion regulation is analogous to a range of studies that have found self‐regulation to be a mediator between religiousness and adolescent risk‐taking (see Holmes & Kim‐Spoon, 2016a for a review). Importantly, by simultaneously considering the two primary dimensions of self‐regulation as parallel mediators, this study sheds light on the specific pathway through which religiousness contributes to demoting adolescent risk‐taking.…”
Section: Discussionsupporting
confidence: 71%
“…However, low alphas tend to underestimate effects, thus effects found in this study could have been stronger, not weaker, if the scores had demonstrated higher reliability (e.g., Furr & Bacharach, ). Finally, the lack of direct association between religiousness at Time 1 and risk‐taking at Time 3 is surprising, given the prior finding of modest yet robust association between religiousness and externalizing behaviors (e.g., Holmes & Kim‐Spoon, 2016a). In this community sample of early to middle adolescents, risk‐taking behavior prevalence was relatively low, resulting in limited variance, which may have contributed to the dampened longitudinal effect of religiousness.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering that the majority of adolescents in the United States have a religious affiliation (Funk & Smith, 2012), believe in God, and attend religious services at least twice a month (Denton, Pearce & Smith, 2008), it is not surprising that the Introjector group is the majority in the current sample. Indeed, a recent study showed that adolescents’ higher introjection was linked to higher substance use as well as lower self-regulation (Holmes & Kim-Spoon, 2016a). Those who look to understand individuals’ R/S beliefs should be careful to note how well integrated these beliefs are to their lives and understand that simply acknowledging R/S belief does not necessarily bestow its beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on adolescent R/S and psychopathology generally points to a negative relationship (Hackney & Sanders, 2003; Hill & Pargament, 2003; Kelly, Polanin, Jang & Johnson, 2015; King & Furrow, 2004; see Chitwood, Weis, & Leukefeld, 2008 and Holmes & Kim-Spoon, 2016a for reviews); however, fewer studies have examined specifically interactive effects of R/S measures on outcomes. Available studies examining interactive effects have revealed inconsistent findings trends.…”
Section: Adolescent Religiousness and Psychopathologymentioning
confidence: 99%